Probing the effect of selenium substitution in kesterite-Cu2ZnSnS4 nanocrystals prepared by hot injection method - Pandharkar, Subhash; Rondiya, Sachin; Bhorde, Ajinkya; Nair, Shruthi; Aher, Rahul; Vairale, Priti; Waghmare, Ashish; Naik, Dhirsing; Waykar, Ravindra; Jadhav, Yogesh (Journal of Materials Science-Materials in Electronics, 2019)
In this paper, we report the effect of sulfur (S) substitution with selenium (Se) in CZTS nanocrystals prepared by hot injection method. The formation of kesterite-copper zinc tin sulfide (Cu2ZnSnS4, CZTS) and copper zinc tin selenide (Cu2ZnSnSe4, CZTSe) nanocrystals is confirmed by X-ray diffraction (XRD), Raman spectroscopy and transmission electron microscopy (TEM) analysis. The XRD, TEM and atomic force microscopy (AFM) analysis shows an overall increase in average crystallite size upon Se substitution. AFM images revealed an increase in root mean square surface roughness (S-q) and average surface roughness (S-a) when S in CZTS is replaced by Se. The substitution of S by Se in host CZTS narrows the optical band gap from 1.56 to 1.03 eV. The ultraviolet photoelectron spectroscopy (UPS) analysis shows shift in valence band and conduction band edge in CZTSe compared to CZTS. The photocurrent density measurement in synthesized CZTSe thin films is similar to 4 to 5 times higher than CZTS thin films. The obtained results show that CZTSe can be a promising candidate as absorber material in photovoltaic applications.

Lead-free Cs2AgBiCl6 double perovskite: experimental and theoretical insights into the self-trapping for optoelectronic applications - Rahane, Swati N.; Rahane, Ganesh K.; Mandal, Animesh; Jadhav, Yogesh; Godha, Akshat; Rokade, Avinash; Shah, Shruti; Hase, Yogesh; Waghmare, Ashish; Saykar, Nilesh G.; Roy, Anurag; Salgaonkar, Kranti N.; et al. (ACS Physical Chemistry Au, 2024)
Lead-free double perovskites (DPs) will emerge as viable and environmentally safe substitutes for Pb-halide perovskites, demonstrating stability and nontoxicity if their optoelectronic property is greatly improved. Doping has been experimentally validated as a powerful tool for enhancing optoelectronic properties and concurrently reducing the defect state density in DP materials. Fundamental understanding of the optical properties of DPs, particularly the self-trapped exciton (STEs) dynamics, plays a critical role in a range of optoelectronic applications. Our study investigates how Fe doping influences the structural and optical properties of Cs2AgBiCl6 DPs by understanding their STEs dynamics, which is currently lacking in the literature. A combined experimental–computational approach is employed to investigate the optoelectronic properties of pure and doped Cs2AgBiCl6 (Fe–Cs2AgBiCl6) perovskites. Successful incorporation of Fe3+ ions is confirmed by X-ray diffraction and Raman spectroscopy. Moreover, the Fe–Cs2AgBiCl6 DPs exhibit strong absorption from below 400 nm up to 700 nm, indicating sub-band gap state transitions originating from surface defects. Photoluminescence (PL) analysis demonstrates a significant enhancement in the PL intensity, attributed to an increased radiative recombination rate and higher STE density. The radiative kinetics and average lifetime are investigated by the time-resolved PL (TRPL) method; in addition, temperature-dependent PL measurements provide valuable insights into activation energy and exciton–phonon coupling strength. Our findings will not only deepen our understanding of charge carrier dynamics associated with STEs but also pave the way for the design of some promising perovskite materials for use in optoelectronics and photocatalysis.